Prevalence and factors associated with vitamin A deficiency in children and adolescents - Rita de Cássia Ribeiro-Silva; Itaciara L. Nunes; Ana Marlúcia Oliveira Assis (Elsevier, 2014)
Objective: To identify the prevalence and factors associated with vitamin A deficiency (VAD) in children and adolescents. Methods: This was a cross-sectional study involving 546 schoolchildren, aged between 7 and 14 years, of both genders, enrolled in public elementary schools. Blood was collected for measurement of serum retinol. The retinol concentration in the samples was determined by high performance liquid chromatography (HPLC). Data were collected on anthropometrics, dietary, demographic, and socioeconomic factors. Polytomous logistic regression was used to evaluate the associations of interest. Results: Approximately 27.5% of the students had retinol values < 30 μg/dL. The multivariate analysis showed, after the appropriate adjustments, a positive and statistically significant association of moderate/severe VAD (OR = 2.19; 95% CI 1.17 to 4.10) and marginal VAD (OR = 2.34; 95% CI 1.47 to 3.73) with age < 10 years. There was also association of VAD moderate/severe (OR = 2.01; 95% CI 1.01 to 5.05) and borderline VAD (OR = 2.14; 95% CI: 1.08 to 4.21) with the anthropometric status of underweight. Lower intake of retinol was detected among those with severe VAD. Conclusion: VAD is a health concern among children and adolescents. Lower weight and younger schoolchildren had greater vulnerability to VAD. Resumo: Objetivo: Identificar prevalência e fatores associados à deficiência de vitamina A (DVA) entre crianças e adolescentes. Métodos: Estudo transversal envolvendo 546 escolares, com idade entre 7 e 14 anos, de ambos os sexos, matriculadas na rede pública do ensino fundamental. O sangue foi coletado para dosagem dos níveis séricos de retinol. A concentração de retinol das amostras foi determinada pelo método da cromatografia líquida de alta eficiência (CLAE). Coletaram-se dados antropométricos, alimentares, demográficos e socioeconômicos. Utilizou-se da regressão logística politômica para avaliar as associações de interesse. Resultados: Aproximadamente 27,5% dos estudantes apresentaram valores de retinol < 30 μg/dL. Em análise multivariada, verificou-se, após devidos ajustes, associação positiva e estatisticamente significante da DVA moderada/grave (OR = 2,19; IC 95%: 1,17-4,10) e da DVA marginal (OR = 2,34; IC 95%: 1,47-3,73) com a idade < 10anos. Verificou-se, igualmente, associação da DVA moderada/grave (OR = 2,01; IC 95%: 1,01-5,05) e DVA marginal (OR = 2,14; IC 95%: 1,08-4,21) com o estado antropométrico magreza. Menor consumo de retinol foi detectado entre aqueles com DVA grave. Conclusão: A deficiência de vitamina A configura-se como um problema de saúde preocupante entre os escolares e adolescentes. Constatou-se maior vulnerabilidade dos escolares de baixo peso e mais jovens à DVA. Keywords: Vitamin A deficiency, Risk factors, Children, Adolescents, Palavras-chave: Deficiência de vitamina A, Fatores de risco, Crianças, Adolescentes